Optical element, optical system, and optical device
A multilayer antireflection film with silicon oxide and magnesium fluoride layers enhances the mechanical strength and durability of resin-based optical elements, addressing the issues of stress-related cracking and peeling.
Patent Information
- Application Number
- JP2020181840
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-10-29
- Publication Date
- 2024-12-16
- Estimated Expiration
- 2040-10-29
AI Technical Summary
Existing antireflection films on resin-based optical elements suffer from low mechanical strength and environmental durability due to the strong tensile stress of magnesium fluoride, leading to cracks or peeling.
A multilayer antireflection film structure is devised, where silicon oxide layers are used as the first and third layers, with a magnesium fluoride layer in between, and the layers are optimized to balance stress and adhesion, using a vapor deposition method to enhance film strength and durability.
The multilayer film structure provides optical elements with high mechanical strength and environmental durability, maintaining low reflectance and resisting cracking or peeling under various conditions.
Smart Images

Figure 0007599910000019 
Figure 0007599910000020 
Figure 0007599910000021
Abstract
Description
[Technical field]
[0001] The present invention relates to an optical element. [Background technology]
[0002] Patent Document 1 discloses an anti-reflection coating formed with an outermost layer being a layer mainly composed of SiO2 or SiO (silicon oxide layer) and the next layer being a layer mainly composed of MgF2 (magnesium fluoride layer). Patent Document 2 discloses an anti-reflection coating composed of a multilayer in which silicon oxide layers and tantalum oxide layers are alternately laminated, a magnesium fluoride layer formed on the multilayer, and a silicon oxide layer formed on the magnesium fluoride layer as the outermost layer. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2002-202401 A [Patent Document 2] JP 2017-134404 A Summary of the Invention [Problem to be solved by the invention]
[0004] However, in the anti-reflection coating configurations described in Patent Documents 1 and 2, it is difficult to improve the mechanical strength and environmental durability of the optical element because of the high tensile stress of magnesium fluoride, which may result in film cracking and peeling of the anti-reflection coating on the lens made of a resin material.
[0005] SUMMARY OF THE PRESENT EMBODIMENTS The present invention has an object to provide an optical element, an optical system, and an optical device that have high mechanical strength and environmental durability. [Means for solving the problem]
[0006] An optical element according to one aspect of the present invention is an optical element having a substrate made of a resin material and an antireflection coating, the antireflection coating comprising a first coating formed on the substrate and a second coating formed on the first coating, the second coating comprising a first layer, a second layer, and a third layer arranged in that order from the side closest to the first coating, the second layer containing magnesium fluoride, and each of the first layer and the third layer containing 90% or more by weight of magnesium fluoride. two Contains silicon oxide and up to 10% aluminum by weight.
[0007] Other objects and features of the present invention will be described in the following embodiments. Effect of the Invention
[0008] According to the present invention, it is possible to provide an optical element, an optical system, and an optical device having high mechanical strength and environmental durability. [Brief description of the drawings]
[0009] [Figure 1] 2 is a schematic cross-sectional view of an optical element in each example. [Diagram 2] 1 shows the reflectance characteristics of the optical element in Example 1 at an incident angle of 0 degrees. [Diagram 3] 13 shows the reflectance characteristics of the optical element in Example 2 at an incident angle of 0 degrees. [Figure 4] 13 shows the reflectance characteristics of the optical element in Example 3 at an incident angle of 0 degrees. [Diagram 5] 13 shows the reflectance characteristics of the optical element in Example 4 at an incident angle of 0 degrees. [Figure 6] 13 shows the reflectance characteristics of the optical element in Example 5 at an incident angle of 0 degrees. [Figure 7] 13 shows the reflectance characteristics of the optical element in Example 6 at an incident angle of 0 degrees. [Figure 8] 13 shows the reflectance characteristics of the optical element in Example 7 at an incident angle of 0 degrees. [Figure 9] 13 shows the reflectance characteristics of the optical element in Example 8 at an incident angle of 0 degrees. [Figure 10]13 shows the reflectance characteristics of the optical element in Example 9 at an incident angle of 0 degrees. [Figure 11] 13 shows the reflectance characteristics of the optical element in Example 10 at an incident angle of 0 degrees. [Figure 12] 13 shows the reflectance characteristics of the optical element in Example 11 at an incident angle of 0 degrees. [Figure 13] 13 shows the reflectance characteristics of the optical element in Example 12 at an incident angle of 0 degrees. [Figure 14] 13 shows the reflectance characteristics of the optical element in Example 13 at an incident angle of 0 degrees. [Figure 15] 16 shows the reflectance characteristics of the optical element in Example 14 at an incident angle of 0 degrees. [Figure 16] 15 shows the reflectance characteristics of the optical element in Example 15 at an incident angle of 0 degrees. [Figure 17] 13 shows the reflectance characteristics of the optical element in Comparative Example 1 at an incident angle of 0 degrees. [Figure 18] 13 shows the reflectance characteristics of the optical element in Comparative Example 2 at an incident angle of 0 degrees. [Figure 19] FIG. 21 is a cross-sectional view of an optical system in Example 16. [Figure 20] FIG. 23 is an external perspective view of an imaging device according to a seventeenth embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, an embodiment of the present invention will be described in detail with reference to the drawings.
[0011] First, a schematic configuration of an optical element 300 in this embodiment will be described with reference to Fig. 1. Fig. 1 is a schematic cross-sectional view showing the optical element 300. The optical element 300 has a transparent resin substrate (base material made of a resin material) 200, and an antireflection film 100 formed on the transparent resin substrate 200. The antireflection film 100 is composed of a multilayer film (first film) 111 and a multilayer film (second film) 101, in that order from the transparent resin substrate 200. That is, the antireflection film 100 is composed of the multilayer film 111 formed on the transparent resin substrate 200, and the multilayer film 101 formed on the multilayer film 111 (formed farthest from the transparent resin substrate 200).
[0012] The multilayer film 111 is made up of layers 11, 12, 13, 14, 15, and 16 in order from the transparent resin substrate 200. In this embodiment, the multilayer film 111 is made up of six layers, but is not limited to this. The number of layers in the multilayer film 111 may be any number as long as it is one or more. The multilayer film 101 is made up of three layers, a layer (first layer) 01, a layer (second layer) 02, and a layer (third layer) 03, in order from the side closer to the multilayer film 111. The layers 01 and 03 constituting the multilayer film 101 each contain silicon oxide (SiO2), and the layer 02 contains magnesium fluoride (MgF2). More specifically, the layers 01 and 03 are made up of silicon oxide or are made up of silicon oxide as the main component (a layer containing silicon oxide at a weight ratio of 90% or more). The layer 02 is made up of magnesium fluoride or is made up of magnesium fluoride as the main component.
[0013] When the anti-reflection film 100 is vapor-deposited on the transparent resin substrate 200, it is necessary to perform the film formation while the transparent resin substrate 200 is not heated (or heated at a low temperature of 80 degrees or less). Magnesium fluoride vapor-deposited without heating (or heated at a low temperature of 80 degrees or less) has low film strength and strong tensile stress. On the other hand, silicon oxide vapor-deposited without heating (or heated at a low temperature of 80 degrees or less) has high film strength and also has compressive stress. In this embodiment, by sandwiching a magnesium fluoride layer between silicon oxide layers, as in the configuration of the multilayer film 101, it is possible to improve the film strength and improve adhesion by offsetting the stress.
[0014] In this embodiment, when the refractive indices at the d-line of the layers 01, 02, and 03 are n1, n2, and n3, the physical film thicknesses of the layers 01, 02, and 03 are d1, d2, and d3 (nm), and the wavelength of the d-line is λ, it is desirable to satisfy the following conditional formula (1).
[0015] λ / 8≦n1d1+n2d2+n3d3≦λ / 2 …(1) In this embodiment, it is more desirable to set the numerical range of conditional expression (1) to the following conditional expression (1a).
[0016] λ / 6≦n1d1+n2d2+n3d3≦λ / 3 …(1a) The antireflection performance of the antireflection film 100 is improved by making the outermost layer (uppermost layer) of a material with a lower refractive index and setting the optical film thickness to about λ / 4. In this embodiment, the multilayer film 101 is regarded as a layer substantially equivalent to the low refractive index material of the outermost layer, and by satisfying formula (1), the antireflection performance can be improved.
[0017] In this embodiment, it is desirable to satisfy the following conditional expressions (2) and (3).
[0018] 0.2≦n2d2 / (n1d1+n2d2+n3d3)≦0.9 …(2) 0.5≦n1d1 / n3d3≦2.0 … (3) In this embodiment, it is more desirable to set the numerical ranges of the conditional expressions (2) and (3) as shown in the following conditional expressions (2a) and (3a).
[0019] 0.3≦n2d2 / (n1d1+n2d2+n3d3)≦0.7 …(2a) 0.8≦d1 / d3≦1.2 …(3a) Increasing the thickness of layer 02 in multilayer film 101 decreases the average refractive index of multilayer film 101, but decreases the film strength and makes it difficult to ensure adhesion due to increased tensile stress. On the other hand, increasing the thickness of layers 01 and 03 improves the film strength, decreases the tensile stress, and makes it easier to ensure adhesion, but increases the average refractive index of multilayer film 101. By forming each film thickness so that it satisfies conditional expressions (2) and (3), it is possible to achieve both anti-reflection performance and film strength.
[0020] The transparent resin substrate 200 expands due to an increase in temperature. Magnesium fluoride has a large tensile stress. Generally, a vapor-deposited film of silicon oxide has a compressive stress, but a stronger compressive stress is required to offset the stress of magnesium fluoride. In this embodiment, therefore, a silicon oxide material containing a trace amount of aluminum is used to increase the compressive stress. For this reason, it is preferable that the material constituting the layers 01 and 03 is a material containing silicon oxide as a main component and a trace amount of aluminum. For this reason, it is preferable that the refractive indexes n1 and n3 satisfy the following conditional expressions (4) and (5), respectively.
[0021] 1.4≦n1≦1.5 …(4) 1.4≦n3≦1.5 …(5) Moreover, it is preferable that the layers 01 and 03 contain aluminum at a weight ratio of 10% or less. Even a very small amount of aluminum is effective. Even a silicon oxide film containing 0.001% aluminum by weight can prevent film cracking and peeling when combined with a magnesium fluoride film.
[0022] The multilayer film 111 may be a combination of a high refractive index material and a medium refractive index material (having a refractive index for the d-line of about 1.6 to 1.8), but is preferably a layer (alternating layer) in which a high refractive index material and a low refractive index material are alternately laminated. The high refractive index material used in the multilayer film 111 is preferably a material whose main component is any one of tantalum oxide, titanium oxide, lanthanum oxide, and zirconia oxide, or a mixture of a plurality of these. The high refractive index material has tensile stress. The low refractive index material used in the multilayer film 111 is preferably the same material as the layers 01 and 03 from the viewpoints of ease of fabrication and offsetting the stress of the anti-reflection film 100. Since the high refractive index material has tensile stress and the low refractive index material has compressive stress, the stress is offset by forming the alternating layers. The alternating layers are not limited to the six layers shown in FIG. 1, and may be one layer of at least two types of materials.
[0023] The layer 11, which is the bottom layer of the multilayer film 111, may be made of the same material as the layers 01 and 03. The transparent resin substrate 200 generally has a larger thermal expansion coefficient than glass. By using a material with high compressive stress on the transparent resin substrate 200, the layer 11 can follow the shape change that occurs when the transparent resin substrate 200 expands due to high temperatures, and film cracking can be prevented.
[0024] The method of forming the anti-reflection film 100 consisting of the multilayer film 111 and the multilayer film 101 is not particularly limited as long as it is a physical vapor deposition method such as a vapor deposition method, a sputtering method, or an ion plating method. In particular, the vapor deposition method is more preferable because fluoride is less likely to decompose. In the vapor deposition method, methods of heating the vapor deposition material include a resistance heating method, an electron beam vapor deposition method, and a laser vapor deposition method. The electron beam vapor deposition method is more preferable because it can directly heat the film material, so that the film can be formed on the substrate without heating, there is little contamination, and the quality of the film is relatively high. It is also preferable to use an ion beam assist method. By using an independent ion source to assist the vapor deposition, a dense film with low absorption and scattering and high strength can be formed.
[0025] In this embodiment, when the refractive index (average refractive index at the d line) of the transparent resin substrate 200 is nd, it is desirable to satisfy the following conditional expression (6).
[0026] 1.48≦nd≦1.80 In this embodiment, the linear expansion coefficient of the transparent resin substrate 200 is α(10 -5 / ° C., it is desirable to satisfy the following conditional expression (7):
[0027] 1.5≦α≦30.0 Each embodiment will now be described in detail. EXAMPLES
[0028] FIG. 1 is a schematic cross-sectional view of an optical element 300 according to a first embodiment of the present invention. The optical element 300 of this embodiment is an optical element in which an anti-reflection film 100 is formed on a transparent resin substrate 200. The transparent resin substrate 200 is a COP resin (ZEONEX, manufactured by Zeon Corporation) with a refractive index of 1.53 (d-line). As the layer materials, layers 11, 13, 15, 01, and 03 are made of SiO2, layers 12, 14, and 16 are made of a mixture of ZrO2 and TiO2, and layer 02 is made of MgF2. Table 1 shows the details of the film configuration of the optical element of this embodiment. The refractive index and film thickness of each material satisfy the formulas (1), (2), and (3).
[0029] The method for forming the anti-reflection film 100 of this embodiment is as follows. The anti-reflection film 100 is formed by a deposition method. An electron beam is used to heat the evaporation material. In addition, an ion beam assisted deposition method is used to form a denser film. The inside of the vacuum chamber of the deposition device is filled with 2×10 -3 The vacuum chamber was evacuated without heating until it reached a high vacuum of approximately 1×10 Pa. After it was confirmed that the inside of the vacuum chamber had reached a high vacuum state, Ar was introduced into the ion gun as an inert gas, and the ion gun was made to discharge. After the ion gun reached a stable state, oxygen was introduced into the vacuum chamber until the vacuum pressure reached 1×10 -2 Ion-assisted deposition is performed using oxygen ions at approximately 1000 Pa.
[0030] Fig. 2 shows the reflectance characteristics of the optical element in this example. In Fig. 2, the horizontal axis represents wavelength (nm) and the vertical axis represents reflectance (%). In the wavelength range of 420 to 680 nm, the reflectance is 0.25% or less, which is an extremely good characteristic.
[0031] The layer 02 made of magnesium fluoride is non-thermal evaporated, has low strength, and has high tensile stress. On the other hand, non-thermal evaporated silicon oxide is strong and has compressive stress. The multilayer film 101, in which the magnesium fluoride film is sandwiched between the silicon oxide films, has high strength as a whole, and the stress is offset, so that it is a film with excellent environmental reliability that does not crack or peel off.
[0032] In order to confirm the durability of the antireflection film 100 under various conditions, the following durability tests were carried out. (High temperature and humidity storage test) The prepared sample was left in a thermostatic chamber set at a temperature of 60° C. and a humidity of 90% for 1000 hours, and then the appearance of the anti-reflection film 100 was visually observed. (Low temperature storage test) The prepared sample was left in a thermostatic chamber set at a temperature of −30° C. for 1000 hours, and then the appearance of the anti-reflection film 100 was visually observed. (High temperature storage test) The prepared sample was left in a thermostatic chamber set at 70° C. for 12 hours, and then the appearance of the anti-reflection film 100 was visually observed. (Adhesion test) An adhesive tape was applied to the surface of the anti-reflection film 100 of the sample, and then the tape was peeled off in a direction perpendicular to the film surface. This was repeated five times, and visual inspection was performed to see whether the film had peeled off. (Surface hardness test) The anti-reflection film 100 was rubbed back and forth 10 times with a solvent-soaked Silbon paper under a load of about 200 g, and then the appearance of the anti-reflection film 100 was visually observed.
[0033] The results of the durability tests are shown in Table 18. In all tests, no film cracking or peeling occurred, confirming that a good anti-reflection coating was formed.
[0034] [Table 1] EXAMPLES
[0035] The optical element of Example 2 is manufactured using the same transparent resin substrate, the same deposition material, and the same deposition conditions as those of Example 1. Table 2 shows the details of the film configuration of the optical element of this example. The refractive index and film thickness of each material satisfy the formulas (1), (2), and (3). FIG. 3 shows the reflectance characteristics of the optical element of this example. In FIG. 3, the horizontal axis shows the wavelength (nm) and the vertical axis shows the reflectance (%). In the wavelength range of 420 to 680 nm, the reflectance is 0.25% or less, which is an extremely good characteristic.
[0036] The results of the durability tests are shown in Table 18. In all tests, no film cracking or peeling occurred, confirming that a good anti-reflection coating was formed.
[0037] [Table 2] EXAMPLES
[0038] The transparent resin substrate 200 of the third embodiment is a special PC resin (Mitsui Gas Chemical Co., Ltd. "EP-5000"). As for the layer materials, the layers 11, 13, 15, 01, and 03 are made of SiO2 containing 0.001% by weight of Al, the layers 12, 14, and 16 are made of a mixture of Ta2O5 and TiO2, and the layer 02 is made of MgF2. Table 3 shows the details of the film configuration of the optical element of the present embodiment. The refractive index and film thickness of each material satisfy the formulas (1), (2), and (3). The anti-reflection film 100 of the present embodiment is formed by the electron beam deposition method and the ion-assisted deposition method, as in the first embodiment. FIG. 4 shows the reflectance characteristics of the optical element of the present embodiment. In FIG. 4, the horizontal axis indicates the wavelength (nm) and the vertical axis indicates the reflectance (%). In the wavelength range of 420 to 680 nm, the reflectance is 0.25% or less, which is a very good characteristic.
[0039] The results of the durability tests are shown in Table 18. In all tests, no film cracking or peeling occurred, confirming that a good anti-reflection coating was formed.
[0040] In this embodiment, the layers 01 and 03 are SiO2 layers containing 0.001% Al by weight. This layer has a very strong compressive stress. MgF2 has a very strong tensile stress, and the resin material has a strong tendency to expand. According to this embodiment, these stresses are offset, so that an anti-reflection film with very high environmental durability can be provided.
[0041] [Table 3] EXAMPLES
[0042] The transparent resin substrate 200 of Example 4 is a special PC resin (Mitsui Gas Chemical Co., Ltd. "EP-5000"). As for the layer materials, layers 12, 14, 01, and 03 are made of SiO2 containing 1.0% by weight of Al, layers 11, 13, and 15 are made of a mixture of ZrO2 and TiO2, and layer 02 is made of MgF2. Table 4 shows the details of the film configuration of the optical element of this example. The refractive index and film thickness of each material satisfy the formulas (1), (2), and (3). Figure 5 shows the reflectance characteristics of the optical element of this example. In Figure 5, the horizontal axis indicates the wavelength (nm) and the vertical axis indicates the reflectance (%). In the wavelength range of 420 to 680 nm, the reflectance is 0.3% or less, which is an extremely good characteristic.
[0043] The results of the durability tests are shown in Table 18. In all tests, no film cracking or peeling occurred, confirming that a good anti-reflection coating was formed.
[0044] [Table 4] EXAMPLES
[0045] The transparent resin substrate 200 of Example 5 is made of COP resin (ZEONEX, manufactured by Zeon Corporation). As for the layer materials, layers 11, 13, 15, 01, and 03 are made of SiO2 containing 2.0% by weight of Al, layers 12, 14, and 16 are made of a mixture of Ta2O5 and TiO2, and layer 02 is made of MgF2. Table 5 shows the details of the film configuration of the optical element of this example. The refractive index and film thickness of each material satisfy the formulas (1), (2), and (3). FIG. 6 shows the reflectance characteristics of the optical element of this example. In FIG. 6, the horizontal axis indicates the wavelength (nm) and the vertical axis indicates the reflectance (%). In the wavelength range of 420 to 680 nm, the reflectance is 0.25% or less, which is a very good characteristic.
[0046] The results of the durability tests are shown in Table 18. In all tests, no film cracking or peeling occurred, confirming that a good anti-reflection coating was formed.
[0047] [Table 5] EXAMPLES
[0048] The transparent resin substrate 200 of Example 6 is made of COP resin (ZEONEX, manufactured by Zeon Corporation). As for the layer materials, layers 11, 13, 15, 01, and 03 are made of SiO2 containing 3.0% by weight of Al, layers 12, 14, and 16 are made of a mixture of Ta2O5 and TiO2, and layer 02 is made of MgF2. Table 6 shows the details of the film configuration of the optical element of this example. The refractive index and film thickness of each material satisfy the formulas (1), (2), and (3). FIG. 7 shows the reflectance characteristics of the optical element of this example. In FIG. 7, the horizontal axis shows the wavelength (nm) and the vertical axis shows the reflectance (%). In the wavelength range of 420 to 680 nm, the reflectance is 0.3% or less, which is an extremely good characteristic.
[0049] The results of the durability tests are shown in Table 18. In all tests, no film cracking or peeling occurred, confirming that a good anti-reflection coating was formed.
[0050] [Table 6] EXAMPLES
[0051] The transparent resin substrate 200 of Example 7 is made of COP resin (ZEONEX, manufactured by Zeon Corporation). As for the layer materials, layers 12, 14, 01, and 03 are made of SiO2 containing 2.0% by weight of Al, layers 11, 13, and 15 are made of a mixture of Ta2O5 and TiO2, and layer 02 is made of MgF2. Table 7 shows the details of the film configuration of the optical element of this example. The refractive index and film thickness of each material satisfy the formulas (1), (2), and (3). FIG. 8 shows the reflectance characteristics of the optical element of this example. In FIG. 8, the horizontal axis indicates the wavelength (nm) and the vertical axis indicates the reflectance (%). In the wavelength range of 420 to 680 nm, the reflectance is 0.3% or less, which is an extremely good characteristic.
[0052] The results of the durability tests are shown in Table 18. In all tests, no film cracking or peeling occurred, confirming that a good anti-reflection coating was formed.
[0053] [Table 7] EXAMPLES
[0054] The transparent resin substrate 200 of Example 8 is a special PC resin (Mitsui Gas Chemical Co., Ltd. "EP-5000"). As for the layer materials, layers 11, 13, 15, 01, and 03 are made of SiO2 containing 3.0% by weight of Al, layers 12, 14, and 16 are made of a mixture of Ta2O5 and TiO2, and layer 02 is made of MgF2. Table 8 shows the details of the film configuration of the optical element of this example. The refractive index and film thickness of each material satisfy the formulas (1), (2), and (3). Figure 9 shows the reflectance characteristics of the optical element of this example. In Figure 9, the horizontal axis indicates the wavelength (nm) and the vertical axis indicates the reflectance (%). In the wavelength range of 420 to 680 nm, the reflectance is 0.25% or less, which is a very good characteristic.
[0055] The results of the durability tests are shown in Table 18. In all tests, no film cracking or peeling occurred, confirming that a good anti-reflection coating was formed.
[0056] [Table 8] EXAMPLES
[0057] The transparent resin substrate 200 of Example 9 is a special PC resin (Mitsui Gas Chemical Co., Ltd. "EP-5000"). As for the layer materials, layers 11, 13, 15, 01, and 03 are made of SiO2 containing 2.5% by weight of Al, layers 12, 14, and 16 are made of a mixture of Ta2O5 and TiO2, and layer 02 is made of MgF2. Table 9 shows the details of the film configuration of the optical element of this example. The refractive index and film thickness of each material satisfy the formulas (1), (2), and (3). Figure 10 shows the reflectance characteristics of the optical element of this example. In Figure 10, the horizontal axis indicates the wavelength (nm) and the vertical axis indicates the reflectance (%). In the wavelength range of 420 to 680 nm, the reflectance is 0.3% or less, which is a very good characteristic.
[0058] The results of the durability tests are shown in Table 18. In all tests, no film cracking or peeling occurred, confirming that a good anti-reflection coating was formed.
[0059] [Table 9] EXAMPLES
[0060] The transparent resin substrate 200 of Example 10 is a COP resin (ZEONEX, manufactured by Zeon Corporation). As for the layer materials, layers 11, 13, 15, 01, and 03 are made of SiO2 containing 4.5% by weight of Al, layers 12, 14, and 16 are made of a mixture of Ta2O5 and TiO2, and layer 02 is made of MgF2. Table 10 shows the details of the film configuration of the optical element of this example. The refractive index and film thickness of each material satisfy the formulas (1), (2), and (3). Figure 11 shows the reflectance characteristics of the optical element of this example. In Figure 11, the horizontal axis shows the wavelength (nm) and the vertical axis shows the reflectance (%). In the wavelength range of 420 to 680 nm, the reflectance is 0.3% or less, which is a very good characteristic.
[0061] The results of the durability tests are shown in Table 18. In all tests, no film cracking or peeling occurred, confirming that a good anti-reflection coating was formed.
[0062] [Table 10] EXAMPLES
[0063] The transparent resin substrate 200 of Example 11 is made of COP resin (ZEONEX, manufactured by Zeon Corporation). As for the layer materials, layers 12, 14, 01, and 03 are made of SiO2 containing 5.2% by weight of Al, layers 11, 13, and 15 are made of a mixture of Ta2O5 and TiO2, and layer 02 is made of MgF2. Table 11 shows the details of the film configuration of the optical element of this example. The refractive index and film thickness of each material satisfy the formulas (1), (2), and (3). Figure 12 shows the reflectance characteristics of the optical element of this example. In Figure 12, the horizontal axis shows the wavelength (nm) and the vertical axis shows the reflectance (%). In the wavelength range of 420 to 680 nm, the reflectance is 0.3% or less, which is a very good characteristic.
[0064] The results of the durability tests are shown in Table 18. In all tests, no film cracking or peeling occurred, confirming that a good anti-reflection coating was formed.
[0065] [Table 11] EXAMPLES
[0066] The transparent resin substrate 200 of Example 12 is a special PC resin (Mitsui Gas Chemical Co., Ltd. "EP-5000"). As for the layer materials, layers 11, 13, 15, 01, and 03 are made of SiO2 containing 4.5% by weight of Al, layers 12, 14, and 16 are made of a mixture of Ta2O5 and TiO2, and layer 02 is made of MgF2. Table 12 shows the details of the film configuration of the optical element of this example. The refractive index and film thickness of each material satisfy the formulas (1), (2), and (3). Figure 13 shows the reflectance characteristics of the optical element of this example. In Figure 13, the horizontal axis shows the wavelength (nm) and the vertical axis shows the reflectance (%). In the wavelength range of 420 to 680 nm, the reflectance is 0.3% or less, which is a very good characteristic.
[0067] The results of the durability tests are shown in Table 18. In all tests, no film cracking or peeling occurred, confirming that a good anti-reflection coating was formed.
[0068] [Table 12] EXAMPLES
[0069] The transparent resin substrate 200 of Example 13 is a special PC resin (Mitsui Gas Chemical Co., Ltd. "EP-5000"). As for the layer materials, layers 12, 14, 01, and 03 are made of SiO2 containing 10.0% Al by weight, layers 11, 13, and 15 are made of a mixture of Ta2O5 and TiO2, and layer 02 is made of MgF2. Table 13 shows the details of the film configuration of the optical element of this example. The refractive index and film thickness of each material satisfy the formulas (1), (2), and (3). Figure 14 shows the reflectance characteristics of the optical element of this example. In Figure 14, the horizontal axis shows the wavelength (nm) and the vertical axis shows the reflectance (%). In the wavelength range of 420 to 680 nm, the reflectance is 0.3% or less, which is a very good characteristic.
[0070] The results of the durability tests are shown in Table 18. In all tests, no film cracking or peeling occurred, confirming that a good anti-reflection coating was formed.
[0071] [Table 13] EXAMPLES
[0072] The transparent resin substrate 200 of Example 14 is a polyester film (PET resin) (Toray Industries, Inc.'s "Lumirror T60"). As for the layer materials, layers 11, 13, 15, 01, and 03 are made of SiO2 containing 5.2% by weight of Al, layers 12, 14, and 16 are made of a mixture of Ta2O5 and TiO2, and layer 02 is made of MgF2. Table 14 shows the details of the film configuration of the optical element of this example. The refractive index and film thickness of each material satisfy the formulas (1), (2), and (3). Figure 15 shows the reflectance characteristics of the optical element of this example. In Figure 15, the horizontal axis shows the wavelength (nm) and the vertical axis shows the reflectance (%). In the wavelength range of 420 to 680 nm, the reflectance is 0.25% or less, which is a very good characteristic.
[0073] The results of the durability tests are shown in Table 18. In all tests, no film cracking or peeling occurred, confirming that a good anti-reflection coating was formed.
[0074] [Table 14] EXAMPLES
[0075] The transparent resin substrate 200 of Example 15 is a polyester film (PET resin) (Toray Industries, Inc.'s "Lumirror T60"). As for the layer materials, layers 11, 13, 15, 01, and 03 are made of SiO2 containing 5.2% by weight of Al, layers 12, 14, and 16 are made of a mixture of Ta2O5 and TiO2, and layer 02 is made of MgF2. Table 15 shows the details of the film configuration of the optical element of this example. The refractive index and film thickness of each material satisfy the formulas (1), (2), and (3). Figure 16 shows the reflectance characteristics of the optical element of this example. In Figure 16, the horizontal axis shows the wavelength (nm) and the vertical axis shows the reflectance (%). In the wavelength range of 420 to 680 nm, the reflectance is 0.3% or less, which is a very good characteristic.
[0076] The results of the durability tests are shown in Table 18. In all tests, no film cracking or peeling occurred, confirming that a good anti-reflection coating was formed.
[0077] [Table 15] EXAMPLES
[0078] Next, an optical system in Example 16 will be described with reference to FIG. 19. FIG. 19 is a cross-sectional view of an optical system 400. The optical system 400 has a plurality of optical elements G401-G411. 402 is a diaphragm, and 403 is an image forming surface. The optical elements G401-G411 are lenses. At least one of the entrance surface and exit surface of these lenses is provided with an antireflection coating according to any one of Examples 1-15. That is, the optical system 400 has a plurality of optical elements G401-G411, and the plurality of optical elements G401-G411 includes an optical element 300 on which an antireflection coating according to any one of Examples 1-15 is formed.
[0079] The optical system 400 of this embodiment is not limited to an imaging optical system used in an imaging device described later, but can be applied to optical systems for various purposes such as binoculars, projectors, and telescopes. EXAMPLES
[0080] Next, an imaging device in the seventeenth embodiment will be described with reference to Fig. 20. Fig. 20 is a perspective view of the appearance of the imaging device (digital camera 500).
[0081] The digital camera 500 has a camera body 502 and a lens device 501 configured integrally with the camera body 502. However, this embodiment is not limited to this, and the lens device 501 may be an interchangeable lens that is detachable from the camera body 502 for a single-lens reflex camera, a mirrorless camera, or the like. The lens device 501 has the optical system 400 of any one of the embodiments 1 to 15. The camera body 502 has an image sensor 503 such as a CMOS sensor or a CCD sensor. The image sensor 503 is disposed on the imaging plane 403 of the optical system 400.
[0082] Comparative Example 1 Comparative Example 1 is produced under the same deposition conditions as Example 10, using the same deposition material and the same transparent resin substrate. Table 16 shows the film configuration of the optical element of this comparative example. The multilayer film 101 is formed only of a magnesium fluoride layer. FIG. 17 shows the reflectance characteristics of the optical element of this comparative example. In FIG. 17, the horizontal axis shows wavelength (nm) and the vertical axis shows reflectance (%). In the wavelength range of 420 to 680 nm, the reflectance is 0.2 or less, achieving a lower reflectance than Examples 1 to 15.
[0083] The results of the durability test are shown in Table 18. The outermost layer of this comparative example is formed of a magnesium fluoride film, which has low strength. Therefore, in the configuration of this comparative example, film cracks and peeling occurred in each durability test, making it unsuitable for use as an anti-reflection film.
[0084] [Table 16]
[0085] Comparative Example 2 Comparative Example 2 is produced using the same deposition material and transparent resin substrate as Example 10 under the same deposition conditions. Table 17 shows the film configuration of the optical element of this comparative example. The multilayer film 101 is formed only of a silicon oxide layer.
[0086] The results of the durability tests are shown in Table 18. The outermost layer of this comparative example is formed of a silicon oxide film, which has high strength. Therefore, no film cracks or peeling occurred in each durability test.
[0087] Fig. 18 shows the reflectance characteristics of this comparative example. In Fig. 18, the horizontal axis indicates wavelength (nm) and the vertical axis indicates reflectance (%). In the wavelength range of 420 to 680 nm, the reflectance is about 0.5%, which is higher than the reflectances of Examples 1 to 15. For this reason, the configuration of this comparative example may cause ghosts and flares.
[0088] [Table 17]
[0089] [Table 18]
[0090] According to each embodiment, it is possible to provide an optical element, an optical system, and an optical device having high mechanical strength and environmental durability.
[0091] Although the preferred embodiments of the present invention have been described above, the present invention is not limited to these embodiments, and various modifications and changes are possible within the scope of the gist of the present invention. [Explanation of symbols]
[0092] 100 Anti-reflection coating 101 Multilayer film (second film) 111 Multilayer film (first film) 200 Transparent resin substrate (substrate made of resin material) 300 Optical Elements
Claims
1. An optical element having a substrate made of a resin material and an anti-reflection film, the anti-reflection film comprises a first film formed on the substrate and a second film formed on the first film, the second film includes a first layer, a second layer, and a third layer arranged in this order from the side closest to the first film; the second layer comprises magnesium fluoride; 1. An optical element, wherein each of the first layer and the third layer contains 90% or more silicon dioxide by weight and 10% or less aluminum by weight.
2. When the refractive indices of the first to third layers with respect to the d-line are n1, n2, and n3, the physical film thicknesses of the first to third layers are d1 (nm), d2 (nm), and d3 (nm), and the wavelength of the d-line is λ (nm), λ / 8≦n1d1+n2d2+n3d3≦λ / 2 2. The optical element according to claim 1, which satisfies the following condition:
3. λ / 6≦n1d1+n2d2+n3d3≦λ / 3 3. The optical element according to claim 2, which satisfies the following condition:
4. When the refractive indices of the first to third layers with respect to the d line are n1, n2, and n3, respectively, and the physical film thicknesses of the first to third layers are d1 (nm), d2 (nm), and d3 (nm), respectively, 0.2≦n2d2 / (n1d1+n2d2+n3d3)≦0.9 0.5≦n1d1 / n3d3≦2.0 4. The optical element according to claim 1, which satisfies the following condition:
5. 0.3≦n2d2 / (n1d1+n2d2+n3d3)≦0.7 0.8≦n1d1 / n3d3≦1.2 5. The optical element according to claim 4, which satisfies the following condition:
6. When the refractive indices of the first and third layers at the d line are n1 and n3, respectively, 1.4≦n1≦1.5 1.4≦n3≦1.5 6. The optical element according to claim 1, which satisfies the following condition:
7. 7. The optical element according to claim 1, wherein the first film is formed by alternately stacking layers made of the materials constituting the first layer and the third layer and layers made of a material containing at least one of tantalum oxide, titanium oxide, lanthanum oxide, and zirconia oxide.
8. When the average refractive index of the resin material with respect to the d line is nd, 1.48≦nd≦1.80 8. The optical element according to claim 1, which satisfies the following condition:
9. When the linear expansion coefficient of the resin material is α (10-5 / °C), 1.5≦α≦30.0 9. The optical element according to claim 1, which satisfies the following condition:
10. A plurality of optical elements are included. An optical system, wherein the plurality of optical elements include the optical element according to claim 1 .
11. An imaging element; An optical device comprising the optical element according to claim 1 .
Citation Information
Patent Citations
Reflection preventing film and plastics optical component equipped with the same
JP2002202401A
Antireflection film, lens, optical system, objective lens, and optical instrument
JP2012053329A
Display device for transparent glazing
JP2016519774A
Optical element and method for manufacturing optical element
JP2017134404A
Optical Article Comprising an Antireflective Coating in the Visible Region for Low Luminance Conditions
US20180067338A1
